Gradual Drug Release Membranes and Films Used for the Treatment of Periodontal Disease - Nausica Petrescu; Bogdan Crisan; Ovidiu Aghiorghiesei; Codruta Sarosi; Ioana Codruta Mirica; Ondine Lucaciu; Simina Angela Lăcrimioara Iușan; Noemi Dirzu; Dragos Apostu (Membranes, 2022)
Periodontitis is an inflammatory disease that, if not treated, can cause a lot of harm to the oral cavity, to the patients’ quality of life, and to the entire community. There is no predictable standardized treatment for periodontitis, but there have been many attempts, using antibiotics, tissue regeneration techniques, dental scaling, or root planning. Due to the limits of the above-mentioned treatment, the future seems to be local drug delivery systems, which could gradually release antibiotics and tissue regeneration inducers at the same time. Local gradual release of antibiotics proved to be more efficient than systemic administration. In this review, we have made a literature search to identify the articles related to this topic and to find out which carriers have been tested for drug release as an adjuvant in the treatment of periodontitis. Considering the inclusion and exclusion criteria, 12 articles were chosen to be part of this review. The selected articles indicated that the drug-releasing carriers in periodontitis treatment were membranes and films fabricated from different types of materials and through various methods. Some of the drugs released by the films and membranes in the selected articles include doxycycline, tetracycline, metronidazole, levofloxacin, and minocycline, all used with good outcome regarding their bactericide effect; BMP-2, Zinc–hydroxyapatite nanoparticles with regenerative effect. The conclusion derived from the selected studies was that gradual drug release in the periodontal pockets is a promising strategy as an adjuvant for the treatment of periodontal disease.